2016
DOI: 10.1159/000447016
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of Collagen Breakdown by Extracellular Basic pH in Human Dermal Fibroblasts

Abstract: Background/Aims: Wound healing is a complex regeneration process involving the degradation and reassembly of connective tissues and skin layers. Previous studies have shown that pH plays a significant role in both the direct and indirect regulation of cellular processes in the wound, which, in turn, affect the wound healing process. However, the effects of pH on the collagen breakdown component of wound healing have yet to be investigated. Therefore, we investigated the induction of accelerated collagen breakdo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 16 publications
(29 reference statements)
2
22
0
Order By: Relevance
“…The signal transduction pathway that leads to acidic extracellular‐induced MMP9 overexpression is through the activation of phospholipase D and phosphorylation of p38 and MAPK1/2. Park et al showed that cell treatment at pHs 6.04‐6.48 and 7.64‐7.99 leads to MMP‐1 and p38 gene expressions and ROS production . Our data also showed an enhancement of ROS production in face to acidic media.…”
Section: Discussionsupporting
confidence: 73%
“…The signal transduction pathway that leads to acidic extracellular‐induced MMP9 overexpression is through the activation of phospholipase D and phosphorylation of p38 and MAPK1/2. Park et al showed that cell treatment at pHs 6.04‐6.48 and 7.64‐7.99 leads to MMP‐1 and p38 gene expressions and ROS production . Our data also showed an enhancement of ROS production in face to acidic media.…”
Section: Discussionsupporting
confidence: 73%
“…Similarly, our previous study showed that mitogen-activated protein kinase signaling and ROS generation were significantly increased by pH values >7.64 in human fibroblast skin cells or 3HSE [6]. In addition, human fibroblast HS68 cells responded to increased pH toxicity by inducing NADH dehydrogenase activity [6]. To assess whether basic pH increases apoptosis, we measured Annexin V levels.…”
Section: Resultsmentioning
confidence: 96%
“…The 3HSE was established according to previously published methods [6]. Using Neoderm®-ED purchased from TEGO Science (Seoul, South Korea), human dermal fibroblasts (HDF) were cultured in collagen matrix for 1 day.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations